The importance of species range attributes and reserve configuration for the conservatin of angiosperm diversity in Western Australia - Gove, Aaron; Dunn, Robert; Majer, Jonathan (Springer, 2008)
In order to better understand the relationship between reserve design and the species represented by such designs, we examined the effectiveness of the Western Australian reserve system for conserving angiosperm diversity, and examined the characteristics of those species conserved. We overlayed species distribution data for 14 plant lineages with the distribution of the reserve system (8.5% of the State’s area) and identified the species that remained unprotected. We found that, depending upon the method employed, between 174 (5.7%) and 570 (18.7%) of species were not included within the reserve system. Two main unprotected regions were identified, one of which was also a centre of high diversity. Geographical range sizes of unprotected species were six times smaller than those species that were protected, while species richness of small-ranged endemic species coincided with general patterns of species richness. At the level of Western Australia’s bioregions we found that conservation effectiveness was most dependent on characteristics of the reserve system rather than characteristics (size and positioning) of species ranges. At this scale, the most effective way to conserve more species in Western Australia would be to conserve more land, while conservation would be most successful in a uniformly dispersed reserve system. Our results highlight the fact that reserve systems may take on two design approaches based on scale––at continental scales, reserves should be clustered around the hotspots of endemic species, while within regions, an evenly distributed reserve system will most adequately sample species.